MODERN FINANCIAL TECHNOLOGIES AND TRADITIONAL BANKING - Nikolić, Ljubica (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
Contemporary Fintech have revolutionized the world of finance, improved the operations of traditional financial institutions and created a new environment in which banks are no longer the only providers of financial services. Competition between banks today also includes competing banks with new fintech companies and decentralized digital financial sectors. The future appearance of finance will generate, new technological innovations, trust in traditional and decentralized financial sectors, as well as the attitude of monetary authorities towards DeFi systems that for now function outside their control. Compared to banks, the fintech non-banking sector quickly adapts to new business requirements by offering more functional and cheaper digital solutions. DeFi sectors may threaten financial stability and the application of monetary regulation, however, their development can not be stopped. Financial regulation is being extended to digital innovations, but its implementation in native DeFi systems is almost impossible, unlike centralized DeFi platforms whose segments are much easier to legally regulate. The regulation of DeFi makes the international nature of the transfer of financial resources through these networks particularly difficult. An internationally harmonized approach to the regulation of the DeFi sector would provide the best solutions, which is not at all easy to achieve. There is a shift in that direction, after 2008, the regulation of banking and financial markets is slowly losing its exclusively national character and is increasingly adopting solutions based on regional and global financial consensuses, which are still not comprehensive. A hard to reach consensus is also necessary between monetary authorities at the global level and the creators of decentralized financial sectors.
Keywords: modern financial technologies; banking; fintech companies; decentralized finance; advantages; challenges